What Tyndall read: provenance, contents and significance of the Proby Bequest to Carlow Library - DE ARCE, MIGUEL; MaCMILLAN, NORMAN; NEVIN, MARTIN; FLAHAVAN, CARMEL (CARLOW HISTORICAL AND ARCHAEOLOGICAL SOCIETY, 2011)
We give a preliminary description of the provenance and contents of the library that the Tyndalls kept in Hind Head House, in Surrey, and the path it followed to end up in the Carlow County Council Library. For the provenance we draw from unpublished personal accounts and from public aspects of the Tyndall family history, specially from Louisa?s side. The contents of the library comprises about 143 items, between books and pamphlets, which we mention individually, giving in some cases details of the connection between Tyndall and the author of the book. With regard to the significance of the library, we observe that most of the books were British or American editions of Tyndall?s own work, or gifts to Tyndall from other authors who followed on his work, specially with regard to applications of his microbiological findings. We conclude that perhaps Tyndall?s library had more the character of a trophy display-case than a working resource. This would contribute to explain some of the prominent absences in the library?texts from Darwin, or Lucretius, which influenced him profoundly. Buying academic books, when he had them readily available in numerous institutions, might not have been one of Tyndall?s strongest habits, but a look at his home library is nonetheless revealing of Tyndall?s inquisitive and sensitive mind, and of the roots of his personal thinking.
PUBLISHED
Keywords: John Tyndall; Irish Victorian Science